IMPERATIVE SENTENCES IN AMERICAN SERIAL TV GREY’S ANATOMY SEASON 17 - Sabika Qotrunnada Agustina; Tenny Sudjatnika; Ice Sariyati (Journal of English Language Teaching and Literature (JELTL), 2022)
This study focused on analyzing the imperative sentences types and how does it affect the interlocutor that found in the American serial tv Grey’s Anatomy episode 1 of season 17, namely All Tomorrow’s Parties. The researcher uses documentation as data. Meanwhile for the research design, the researcher uses document analysis. For the result of this study, there are three parts of imperative sentence in Grey's Anatomy episode 1 of season 17. They are imperative as command form, imperative as request form, and imperative as suggestion form. Each type of imperative sentence has 2 patterns, namely positive pattern and negative pattern. For imperative as request form, the researcher cannot find any negative pattern. After calculating all the data, the researcher found that imperative as command form is the dominant type of imperative sentences in Grey’s Anatomy. 57,5% of the dialogue appear as command. Meanwhile 17,5% of the dialogue appear as request. It is the least used type of imperative sentences in Grey’s Anatomy episode 1 of season 17. And 25% of the dialogue appear as suggestion. At least a quarter of the dialogue are the imperative as suggestion form.